2020
DOI: 10.1186/s11658-020-00212-1
|View full text |Cite
|
Sign up to set email alerts
|

Unfolded protein response (UPR) integrated signaling networks determine cell fate during hypoxia

Abstract: During hypoxic conditions, cells undergo critical adaptive responses that include the up-regulation of hypoxia-inducible proteins (HIFs) and the induction of the unfolded protein response (UPR). While their induced signaling pathways have many distinct targets, there are some important connections as well. Despite the extensive studies on both of these signaling pathways, the exact mechanisms involved that determine survival versus apoptosis remain largely unexplained and therefore beyond therapeutic control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 276 publications
2
85
0
Order By: Relevance
“…Both the increased ER membrane and the protein folding demand can result in coronavirus-related ER stress and activation of a dedicated signaling pathway, the unfolded protein response (UPR). Importantly, the UPR has the ability to promote cellular survival by increasing ER membranes and folding capacity, but also has the ability to induce cell death if the stress is persistent ( 5 , 8 , 10 , 37 , 45 , 51 , 104 ).…”
Section: Comparison Of the Mirna Target Sites In Human Coronavirusesmentioning
confidence: 99%
“…Both the increased ER membrane and the protein folding demand can result in coronavirus-related ER stress and activation of a dedicated signaling pathway, the unfolded protein response (UPR). Importantly, the UPR has the ability to promote cellular survival by increasing ER membranes and folding capacity, but also has the ability to induce cell death if the stress is persistent ( 5 , 8 , 10 , 37 , 45 , 51 , 104 ).…”
Section: Comparison Of the Mirna Target Sites In Human Coronavirusesmentioning
confidence: 99%
“…The activation of this pathway protects the cell against protein misfolding during hypoxia [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Despite the importance of both HIFs and the UPR pathway for the cancer microenvironment and cardiovascular disorders, the relationship between the HIFs and the UPR is poorly understood, especially in the normal human endothelium [ 12 ]. Although the HIF-dependent activation of the PERK axes has been reported in both cancer and normal cells [ 4 , 13 ], the hypoxic activation of ATF6 and IRE1 signaling remains ambiguous.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in severe cases of COVID-19, hypoxaemia is induced by the pneumonic process and might have several adverse effects in patients (Rello et al, 2020). There are several lines of defence mechanisms in response to hypoxia, which is a consequence of hypoxaemia, including responses triggers from mitochondria and ER (Bartoszewska and Collawn, 2020). The main goal of these responses to hypoxia is restoring oxygen level and promoting cell survival in these conditions (Bartoszewska and Collawn, 2020).…”
Section: Opinionmentioning
confidence: 99%
“…There are several lines of defence mechanisms in response to hypoxia, which is a consequence of hypoxaemia, including responses triggers from mitochondria and ER (Bartoszewska and Collawn, 2020). The main goal of these responses to hypoxia is restoring oxygen level and promoting cell survival in these conditions (Bartoszewska and Collawn, 2020). Therefore, in prolonged hypoxia induction via COVID-19, the UPR is triggered to help the cells to survive.…”
Section: Opinionmentioning
confidence: 99%